Overtraining syndrome in bodybuilding and the difficulty of searching for informative biomarkers for disadaptation diagnostics - Vadym Koval; Anatolii Tsos; Oleh Olkhovyi; Kateryna Drobot; Andrii Chernozub; Vladimir Potop (Фізична реабілітація та рекреаційно-оздоровчі технології, 2025)
Purpose. To study the characteristic features of overtraining syndrome (OTS) in bodybuilding in athletes with different resistance levels and to identify informative blood biomarkers to diagnose disadaptation.